Successful anti‐CD19 CAR T‐cell therapy in HIV‐infected patients with refractory high‐grade B‐cell lymphoma. Issue 21 (10th September 2019) - Abramson, Jeremy S.; Irwin, Kelly E.; Frigault, Matthew J.; Dietrich, Jorg; McGree, Brianne; Jordan, Justin T.; Yee, Andrew J.; Chen, Yi‐Bin; Raje, Noopur S.; Barnes, Jeffrey A.; Davis, Benjamin
Abstract : HIV‐positive patients have been excluded from clinical trials evaluating chimeric antigen receptor (CAR) T‐cell therapies. Herein, the authors report on 2 patients with HIV/AIDS–associated, chemotherapy‐refractory, aggressive B‐cell lymphomas who were treated successfully with the anti‐CD19 CAR T‐cell product axicabtagene ciloleucel.